Українсько-польські порубіжні землі у роки франко-російської війни - Стрільчук, Людмила Василівна; Strilchuk, Liudmyla V. (Волинський краєзнавчий музей, 2014)
Досліджено українсько-польські порубіжні землі у роки франко-російської війни. Проаналізовано франко-російські конфлікти та договори щодо українсько-польських порубіжних територій. Охарактеризовано плани Наполеона щодо українських територій та створення козацьких і селянських ополчень з ініціативи Олександра І. Висвітлено проблеми польсько-українських територій на Віденському конгресі 1814 – 1815 рр.

Explored Ukrainian-Polish fertile lands during the Franco-Russian War. The Franco-Russian conflicts and treaties concerning the Ukrainian-Polish fertile territories are analyzed. The plans of Napoleon concerning Ukrainian territories and the creation of Cossack and peasant militias on the initiative of Alexander I. The problems of the Polish-Ukrainian territories at the Vienna Congress of 1814 - 1815 are described.
Ukraińsko-polskie ziemie pograniczne podczas wojny francusko-rosyjskiej
Ukrainian-Polish fertile lands during the Franco-Russian War
Keywords: українсько-польське порубіжжя; франко-російська війна; тильзитські переговори; козацьке ополчення; Віденський конгрес; Ukrainian-Polish borderlands; Franco-Russian War; Tilsit talks; Cossack militia; Viennese congress